2020
DOI: 10.1103/physrevb.101.134512
|View full text |Cite
|
Sign up to set email alerts
|

Boundary states with elevated critical temperatures in Bardeen-Cooper-Schrieffer superconductors

Abstract: Bardeen-Cooper-Schrieffer (BCS) theory describes a superconducting transition as a single critical point where the gap function or, equivalently, the order parameter vanishes uniformly in the entire system. We demonstrate that in superconductors described by standard BCS models, the superconducting gap survives near the sample boundaries at higher temperatures than superconductivity in the bulk. Therefore, conventional superconductors have multiple critical points associated with separate phase transitions at … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 24 publications
0
29
1
Order By: Relevance
“…We call this enhancement 2 boundary state. It was found in one, two, and three-dimensional superconductors in tight binding BCS model and for one dimensional continuous BCS model [19]. An earlier study of the standard three dimensional continuous BCS model concluded that boundary state is absent: the gap near the boundaries is neither suppressed nor enhanced [17] or weakly suppressed [18].…”
Section: Introductionmentioning
confidence: 95%
“…We call this enhancement 2 boundary state. It was found in one, two, and three-dimensional superconductors in tight binding BCS model and for one dimensional continuous BCS model [19]. An earlier study of the standard three dimensional continuous BCS model concluded that boundary state is absent: the gap near the boundaries is neither suppressed nor enhanced [17] or weakly suppressed [18].…”
Section: Introductionmentioning
confidence: 95%
“…This result can be viewed as a rigorous justification of the numerical observations in [15]. Numerics shows that the ratio T R c pvq{T R c pvq can be as large as 1.06, see [15,Fig. 2].…”
Section: Introduction and Main Resultsmentioning
confidence: 68%
“…This seems to implicitly assume that the effect of the boundary on the critical temperature is negligible. Recent numerical computations [3,15], however, indicate that the Cooper-pair wave function can localize near the boundary, leading to an increase in the critical temperature compared to its bulk value. In this paper, we shall give a rigorous proof of the occurrence of this phenomenon in the simplest setting of one dimension, with δ-interactions among the particles.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
See 2 more Smart Citations